Functional divergence in the proteins encoded by ARO80 from S. uvarum, S. kudriavzevii and S. cerevisiae explain differences in the aroma production during wine fermentation. Issue 8 (10th May 2022) - Tapia, Sebastián M.; Pérez‐Torrado, Roberto; Adam, Ana Cristina; Macías, Laura G.; Barrio, Eladio; Querol, Amparo
Summary: Phenylethanol (PE) and phenylethyl acetate (PEA) are commonly desired compounds in wine because of their rose‐like aroma. The yeast S. cerevisiae produces the PE either through de novo biosynthesis by shikimate pathway followed by the Ehrlich pathway or the direct phenylalanine catabolism via Ehrlich pathway, and then converted into PEA. Previous work demonstrated that, compared to S. cerevisiae, other Saccharomyces species, such as S. kudriavzevii and S. uvarum, produce higher concentrations of PE and PEA from the precursor phenylalanine, which indicates differential activities of the biosynthetic‐involved enzymes. A previous in‐silico analysis suggested that the transcriptional activator Aro80p is one of the best candidates to explain these differences. An improved functional analysis identified significant radical amino acid changes in the S. uvarum and S. kudriavzevii Aro80p that could impact the expression of the catabolic genes ARO9 and ARO10, and hence, the production of PE from phenylalanine. Indeed, wine S. cerevisiae strains carrying the S. uvarum and S. kudriavzevii ARO80 alleles increased the production of both compounds in the presence of phenylalanine by increasing the expression of ARO9 and ARO10 . This study provides novel insights of the unidentified Aro80p regulatory region and the potential usage of alternatives ARO80 alleles to enhance the PE and PEA concentration in wine. Abstract : A functional analysis identified significant radical amino acid changes in the S. uvarum and S. kudriavzevii Aro80p that impact the expression of the catabolic genes ARO9 and ARO10, and hence, the production of phenylethanol from phenylalanine. This study provides novel insights into the Aro80p regulatory region and the potential usage of alternative ARO80 alleles to enhance the phenylethanol from phenylalanine concentration in fermentative beverages.